Agreement between Central Venous and Arterial Blood Gas Measurements in the Intensive Care Unit - Treger, Richard (American Society of Nephrology, 2010)
Background and objectives: Venous blood gas (VBG) analysis is a safer procedure than arterial blood gas (ABG) analysis and may be an alternative for determining acid-base status. The objective of this study was to examine the agreement between ABG and central VBG samples for all commonly used parameters in a medical intensive care unit (ICU) population. Design, setting, participants, & measurements: We performed a single-center, prospective trial to assess the agreement between arterial and central VBG measurements in a medical ICU. Adult patients who were admitted to the ICU and required both a central venous line and an arterial line were enrolled. When an ABG was performed, a central venous sample was obtained to examine the agreement among the pH, Pco(2), and bicarbonate. Data comparing central and peripheral VBG values were also obtained. Results: The mean arterial minus venous difference for pH, Pco(2), and bicarbonate was 0.027, −3.8, and −0.80, respectively. Bland-Altman plots for agreement of pH, Pco(2), and bicarbonate showed 95% limits of agreement of −0.028 to 0.081, −12.3 to 4.8, and −4.0 to 2.4, respectively. Regression equations were derived to predict arterial values from venous values as follows: Arterial pH = −0.307 + 1.05 × venous pH, arterial Pco(2) = 0.805 + 0.936 × venous Pco(2), and arterial bicarbonate = 0.513 + 0.945 × venous bicarbonate. The mean central minus peripheral differences for pH, Pco(2), and bicarbonate were not clinically important. Conclusions: Peripheral or central venous pH, Pco(2), and bicarbonate can replace their arterial equivalents in many clinical contexts encountered in the ICU.